Mothers’ knowledge, attitude and self efficacy of clean home birthing practices in a rural community of Kenya - Mwangi, Julius K.; Pertet, Anne M. (International Journal Of Community Medicine And Public Health, 2018)
Background: In Kenya, approximately 38% of the children are delivered at home. Thus, hygienic practices during home birthing are essential in the prevention of infections to the mother and baby as well as prevention of neonatal deaths. The purpose of our study was to establish mothers’ knowledge, attitude and self-efficacy of clean birthing which would help her influence the behaviour of those assisting her during child birth. We used a correlational, cross-sectional design to examine the relationships knowledge, attitude, and self-efficacy and clean birthing practices. Methods: We collected data using a structured questionnaire through face to face interviews in Olkalou sub-county, Nyandarua County, Kenya. They consisted of 374 mothers of reproductive who had delivered at home six months before the start of the study. Multi-stage sampling technique was used to select the study sample. Likert scale was used to assess attitude and self-efficacy. Results: Close to 2/3rd of the babies were delivered at home by friends, relatives, traditional birth attendants (TBAs) or self-delivered. Cleanliness during home birthing was sub-optimal. Clean home birthing was associated with mothers’ knowledge (odds ratio=1.70) and marital status (OR=2.9). Conclusions: Despite the advocacy on skilled birth attendants, women continue to deliver at home, thus the need to empower mothers with knowledge, positive attitudes and self-efficacy on clean home birthing to reduce infections during childbirth.